The Origin of Laurentia: Rae Craton as the Backstop for Proto-Laurentian Amalgamation by Slab Suction - Hoffman, Paul (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
Proto-Laurentia (i.e. pre-Grenvillian Laurentia) is an aggregate of six or more formerly independent Archean cratons that amalgamated convulsively in geons 19 and 18 (Orosirian Period), along with non-uniformly distributed areas of juvenile Paleoproterozoic crust. Subduction polarities and collision ages have been provisionally inferred between the major cratons (and some minor ones), most recently between the Rae and Hearne cratons. The oldest Orosirian collisions bound the Rae craton: 1.97 Ga (Taltson- Thelon orogen) in the west, and 1.92 Ga (Snowbird orogen) in the southeast. All other Orosirian collision ages in proto-Laurentia are < 1.88 Ga. The Rae craton was the upper plate during (asynchronous) plate convergence at its western and, tentatively, southeastern margins. Subsequent plate convergence in the Wopmay and Trans-Hudson orogens was complex, with the Rae craton embedded in the lower plate prior to the first accretion events (Calderian, Reindeer and Foxe orogenies), but in the upper plate during major subsequent convergence and terminal collisions, giving rise to the Great Bear and Cumberland magmatic arcs, respectively. The ‘orthoversion’ theory of supercontinental succession postulates that supercontinents amalgamate over geoidal lows within a meridional girdle of mantle downwellings, orthogonal to the lingering superswell at the site of the former supercontinent. If the downwelling nodes develop through positive feedback from the descent of cold oceanic slabs, then viscous traction should contribute to drawing the cratons together over the downwelling node. Viewed in this way, the Rae craton was the first to settle over the downwelling node and became the backstop for the other cratons that were drawn towards it by subduction. It was, literally, the origin of Laurentia. Whether the Rae craton was also the origin of Nuna, the hypothetical cogenetic supercontinent, depends on ages and subduction polarities of Orosirian sutures beyond proto-Laurentia.